Evaluating the value of agricultural climate services using hindcast experiments Methods development in India and Bangladesh - Amjath-Babu, Tharayil Shereef; Timsina, Jagadish; Krupnik, Timothy J. (International Maize and Wheat Improvement Center, 2022)
This research note offers insights to a new method for understanding the economic benefits of utilizing climate services for decision making in agriculture, which can provide justification for the public and private investment in provision of climate services to farmers. In order to understand the potential benefits of weather information for improved farm decision making, case studies from wheat farming in India and Bangladesh are presented.